MENINGKATKAN KEMAMPUAN PERKALIAN BAGI ANAK BERKESULITAN BELAJAR MATEMATIKA MELALUI METODE JARIMAGIC - Vella Febrita (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrack: This study aims to test the effectiveness of the use of jarimagic method in improving calculating skill for a child mathematics class learning difficulties SDN 12 Pisang Padang. This research Single Subject Research approach and design of the AB. Subjects were a student learning difficulties in class III. To measure the research variables, the percentage of the techniques applied. Based on the results of data analysis, it was found that the use of jarimagic effective method to improve calculating skills learning disabilities mathematics children in class III SDN 12 Pisang Padang. Kata-kata kunci: Metode Jarimagic; Kemampuan Perkalian; Kesulitan Belajar Matematika